Decolonizing the Museum: Repatriation and Representation in Contemporary Curatorial Practices in France - Paul, Henry Peter (Enigma Institute, 2024)
The contemporary museum landscape in France is undergoing a profound transformation, driven by calls to decolonize its collections and practices. Repatriation of artifacts and rethinking representation are at the forefront of these efforts. This study examines the multifaceted nature of decolonization in French museums, focusing on repatriation initiatives, shifts in curatorial narratives, and the impact of these changes on both institutions and communities. This qualitative research employs a multi-method approach, including; In-depth analysis of repatriation cases from prominent French museums, tracing the process, challenges, and outcomes; Content analysis: Examination of curatorial narratives and exhibition texts, identifying changes in representation and voice; Interviews: Semi-structured interviews with museum professionals, curators, and community representatives, capturing diverse perspectives. The study reveals a complex picture of decolonization in French museums. While repatriation efforts have gained momentum, challenges persist in terms of legal frameworks, provenance research, and intercultural dialogue. Curatorial narratives are gradually shifting towards greater inclusivity, acknowledging historical injustices and incorporating diverse voices. However, the process remains contested, with debates over ownership, authenticity, and the role of museums in society. In conclusion, decolonization is a dynamic and ongoing process in French museums. While repatriation and representation are critical components, they are not sufficient in themselves. The study underscores the need for sustained commitment, transparent communication, and collaborative approaches involving both institutions and communities. Decolonizing the museum necessitates rethinking not only collections but also power structures, narratives, and the very purpose of museums in the 21st century.